2017
DOI: 10.7554/elife.20487
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of embryonic stem cell differentiation inferred from single-cell transcriptomics show a series of transitions through discrete cell states

Abstract: The complexity of gene regulatory networks that lead multipotent cells to acquire different cell fates makes a quantitative understanding of differentiation challenging. Using a statistical framework to analyze single-cell transcriptomics data, we infer the gene expression dynamics of early mouse embryonic stem (mES) cell differentiation, uncovering discrete transitions across nine cell states. We validate the predicted transitions across discrete states using flow cytometry. Moreover, using live-cell microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 67 publications
5
43
0
Order By: Relevance
“…Conversely, classic embryological studies have indicated that cells are canalized to adopt perduring fates separated by epigenetic barriers. Technological limitations necessitated that traditional embryological studies focus on specific fate decisions with selected marker genes, but the advent of single-cell RNA sequencing (scRNA-seq) raises the possibility of fully defining the transcriptomic states of embryonic cells as they acquire their fates (4-8). However, the large number of transcriptional states and branchpoints, as well as the asynchrony in developmental processes, pose major challenges to the comprehensive identification of cell types and the computational reconstruction of their developmental trajectories.…”
mentioning
confidence: 99%
“…Conversely, classic embryological studies have indicated that cells are canalized to adopt perduring fates separated by epigenetic barriers. Technological limitations necessitated that traditional embryological studies focus on specific fate decisions with selected marker genes, but the advent of single-cell RNA sequencing (scRNA-seq) raises the possibility of fully defining the transcriptomic states of embryonic cells as they acquire their fates (4-8). However, the large number of transcriptional states and branchpoints, as well as the asynchrony in developmental processes, pose major challenges to the comprehensive identification of cell types and the computational reconstruction of their developmental trajectories.…”
mentioning
confidence: 99%
“…We studied the differentiation of stem cells both into germ layer progenitors (Jang et al, 2017) and into cortical neurons. To study the latter, we analyzed single-cell gene expression data from 2217 cells from an in vitro differentiation protocol for early human neuronal development (Yao et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Recent efforts in the field have combined predictive computational models with single cell data to elaborate the core GRN network during cell state transitions [34,35]. Recently, this approach has been expanded to connect the core GRN with the essential cues of the extra-cellular environment to predict if, and under what conditions, a cell state transition can be encouraged [36].…”
Section: Stem Cell Bioengineering: Reverse Engineering Of Developmentmentioning
confidence: 99%